Perlindungan hukum pelaku usaha komoditi pertanian melalui penguatan anggaran dalam rangka mencegah krisis pangan - Miftakhul Irfan (Jurnal Cakrawala Hukum, 2021)
The magnitude of the influence of food availability and affordability of prices will provide certainty for the people's trust in the state, especially the Indonesian government, which has Pancasila as the basis for the manifestation of national and state life, must be translated so that its main mission can be understood. In the spirit of a rule of law approach, legal protection for the guarantee of food availability must be considered, so that the main objective of forming a state for the welfare of the people can be realized and felt. Economic democracy based on social justice, which has been translated by economic experts and lawyers into a popular economic model, has a framework that must be clarified. The existence of an agricultural country necessitates a concentration on the agricultural sector. The issue of shrinking agricultural land for food production compared to the area of oil palm land is a manifestation of the weakening role of the government. So that the stimulus to agriculture must be carried out. The application of the cost of food production as well as the guarantee of the lowest price is urgently needed. Of course with a complete explanation that the food problem is not just a guarantee of supply. However, the state's ability to produce independently is the key to state sovereignty.How to cite item: Irfan, M. (2021). Perlindungan hukum pelaku usaha komoditi pertanian melalui penguatan anggaran dalam rangka mencegah krisis pangan. Jurnal Cakrawala Hukum, 12(2), 187-194. doi:https://doi.org/10.26905/idjch.v12i2.5809